A Comparative Study of Initial Involvement in Gangs and Political Extremism. Issue 8 (17th November 2022) - Becker, Michael H.; Decker, Scott H.; LaFree, Gary; Pyrooz, David C.; Ernest, Kyle; James, Patrick A.
ABSTRACT: There is a paucity of research comparing gang members and domestic extremists and extant studies find few explicit linkages. Despite this, there remains a great deal of interest in possible similarities between these criminal groups. Driving this interest is the possibility of adapting policies and practices aimed at preventing entry into criminal groups. A critical first step to determining compatibility is to examine the circumstances of the individuals who enter these organizations and better describe the entry processes. This study provides a unique comparison of entry into these groups by drawing on four broad empirically derived mechanisms of group entry using forty-five in-person interviews of U.S. gang members and thirty-eight life history narratives of individuals who radicalized in the United States. Our results reveal that each of the four conceptual categories appeared to influence initial involvement; however, no single mechanism described involvement in criminal groups or differentiated involvement across the gangs and extremist groups.